Analysis Of Regulatory Quality Worldwide Governance Indicators In Asia Pacific Case Study: Indonesia-Papua New Guinea 2019-2021 - Sahgit Fadila Fadila (Journal of Political Issues)
This study aims to analyze the direction of economic development policies through Regulatory Quality Worldwide Governance Indicators, especially between Indonesia and Papua New Guinea. The selection of the two countries as research subjects is based on the very rapid growth of development between the two countries. As well as, Indonesia and Papua New Guinea have abundant natural resources to be managed in achieving national development so that they become the main investment destination in the Asia and Pacific region.The method used in this research is a qualitative research method by investigating, finding, describing, and explaining the quality or specialty of social influence. The approach used in this research is a case study approach which is a search for data or research information through scientific journals, reference books and available publication materials. Through annual survey data from the Worldbank, namely 2019-2021. It was found that the governments of Indonesia and Papua New Guinea have aggressively developed the rate of economic growth through economic policies in each country. Regulatory Quality is an important instrument for researchers in providing empirical support and validating research findings.